Spherical cactus-like composite based on transition metals Ni, Co and Mn with 1D / 2D bonding heterostructure for electrocatalytic overall water splitting. (10th November 2019) - Zhang, Runzhi; Huang, Lirong; Yu, Zebin; Jiang, Ronghua; Hou, Yanping; Sun, Lei; Zhang, Boge; Huang, Yiyi; Ye, Bo; Zhang, Yalan
Abstract: This paper reports that the spherical cactus-like composite NiCo2 S4 @δ-MnO2 /NF is an effective overall water-splitting bifunctional electrocatalyst consisting of the excellent electrolyzed water material 1D NiCo2 S4 nanowire and 2D layered δ-MnO2 . The innovative catalyst not only has the advantages of 1D nanowires and 2D nanosheets, but also forms 1D/2D bonding heterostructures and spherical cactus-like 3D morphology. Under the synergy of heterostructures and 3D morphology, when the electrolyte is alkaline, the overpotential required in the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER) is low. In addition, when the catalyst is subjected to overall water splitting in a two-electrode system of an alkaline electrolyte, it can also obtain a desired current density at a low overpotential. Moreover, when the material is used in electrolytes with different alkalinity, it demonstrates excellent stability under different electrolytes. A good industrial application prospects can be expected for the transition metal electrocatalyst. Graphical abstract: Image 1 Highlights: Synthesizing a 3D spherical cactus-like composite to increase the ECSA of the material. Combining the advantages of 1D and 2D composite to achieve synergy. Constructing a 1D/2D bonding heterostructure to reduce the Rct of the material, thereby improving the electron transfer efficiency.